Both CYP2C19 and PON1 Q192R Genotypes Influence Platelet Response to Clopidogrel by Thrombelastography in Patients with Acute Coronary Syndrome - Wenxing Peng; Xiujin Shi; Xiaoyu Xu; Yang Lin (Hindawi-Wiley, 2019)
Objective. The objective of this study is to explore the relationships of the effects of CYP2C19 and PON1 Q192R polymorphism on the activity of clopidogrel and the risk of high platelet responsiveness (HPR) by thrombelastography in patients with acute coronary syndrome (ACS). Methods. 459 ACS patients with aspirin and clopidogrel were enrolled in this observational case control study from July 13, 2015, to November 11, 2017. The patients with <30% platelet inhibition were defined as HPR group, while the others were defined as normal platelet responsiveness (NPR) group. The genotypes distribution between the groups was assessed, and the clinical impact of genetic variants was investigated by comparing the relationship between the risk of HPR and genotypes including CYP2C19⁎2, CYP2C19⁎3, CYP2C19⁎17, ABCB1, and PON1. Results. Compared with CYP2C19⁎1/⁎1 wild type carriers, CYP2C19⁎2 and ⁎3 carriers showed a significant association with the lower platelet inhibition (P=0.048). The platelet inhibition in carriers of at least one CYP2C19 loss-of-function (LOF) alleles was obviously higher than noncarriers (P=0.031). The platelet inhibition of PON1 192R carriers was lower than PON1 192Q carriers (P=0.044). Patients with the CYP2C19⁎2 and ⁎3 alleles had a greater risk of HPR than CYP2C19 wild type carriers (adjusted P=0.018 and adjusted P=0.005). At least one PON1 192R carrier predicted a significantly higher risk of HPR than PON1 192Q carriers (adjusted P=0.021). Individual CYP2C19⁎17 and ABCB1 variants did not differ significantly between the two groups. Conclusions. CYP2C19 and PON1 Q192R variants influence ADP-induced platelet inhibition by thrombelastography (TEG) in ACS patients with clopidogrel. In addition, both LOF CYP2C19 and PON1 192R variants are independent risk factors of HPR, which is measured by the relative platelet inhibition.